Democracy’s Deep Roots - Schneider, S. author. aut Link
XIV, 253 p. 9 illus.
Keywords: Does the democratic nation state remain a legitimate regime form in the current age of globalization? This book uses a novel, analytical approach to probe this topical question, drawing on a comparative study of legitimation discourses in the media of four Western democracies (Switzerland, Germany, Britain, and the United States.).